2018
DOI: 10.1002/jcb.27747
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Receptor for advanced glycation end products reveals a mechanism regulating thyroid hormone secretion through the SIRT1/Nrf2 pathway

Abstract: Advanced glycation end products (AGEs) play a causative role in the complications involved with diabetes mellitus (DM). Nowadays, DM with hypothyroidism (DM-hypothyroidism) is indicative of an ascended tendency in the combined morbidity. In this study, we examine the role of the receptor (RAGE) played for AGEs in thyroid hormone (TH) secretion via the silent information regulator 1 (SIRT1)/nuclear factor erythroid-derived factor 2-related factor 2 (Nrf2) pathway. Blood samples were collected from patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Increased risks for metabolic syndrome were associated with a decrease in serum FT4, especially in nonobese adults 25 . Chen et al proposed that advanced glycation end products (AGEs) and high glucose levels exerted a potent effect on cellular damage and thyroid hormone deficiency through AGE upregulation as well as silent mating type information regulation 2 homolog‐1 (SIRT1)/nuclear factor‐E2‐related factor 2 (Nrf2) pathway inactivation 26 . In obese children, hyperthyrotropinemia could already be detected in the prepubertal age, and the increased oxidative stress might represent one of the key regulators of TSH levels 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Increased risks for metabolic syndrome were associated with a decrease in serum FT4, especially in nonobese adults 25 . Chen et al proposed that advanced glycation end products (AGEs) and high glucose levels exerted a potent effect on cellular damage and thyroid hormone deficiency through AGE upregulation as well as silent mating type information regulation 2 homolog‐1 (SIRT1)/nuclear factor‐E2‐related factor 2 (Nrf2) pathway inactivation 26 . In obese children, hyperthyrotropinemia could already be detected in the prepubertal age, and the increased oxidative stress might represent one of the key regulators of TSH levels 27 .…”
Section: Discussionmentioning
confidence: 99%
“…In clinical work, Diabetes mellitus is often found to be coexisted with hypothyroidism [53]. This might be partially related to the upregulation of advanced glycation end products (AGEs), high glucose induce advanced glycation end products receptor (RAGE) and the inactivation of SIRT1/nuclear factor erythroid 2-related factor (NRF2) pathway [54][55][56] (Fig. 2B).…”
Section: Sirt1 Contributes To Neuroendocrine Secretionmentioning
confidence: 99%
“…Wnt signaling pathway was found under control of DNA methylation in our study and was reported to be linked to inflammation, which suggested that DNA methylation of specific genes of Wnt signaling pathway might participated in diabetes-related hypothyroidism [ 28 , 29 ]. Chen et al confirmed that high concentration of glucose inhibited proliferation of Nthy-ori3-1 cells and arrested more thyroid cells in G0/G phase [ 30 ]. This finding suggested that the reduction of thyroid cells might be partly responsible for low thyroid hormone levels.…”
Section: Discussionmentioning
confidence: 99%